2018
DOI: 10.1021/acs.joc.8b01824
|View full text |Cite
|
Sign up to set email alerts
|

Microwave-Enhanced On-Water Amination of 2-Mercaptobenzoxazoles To Prepare 2-Aminobenzoxazoles

Abstract: In this work, we developed a catalyst-free amination of 2-mercaptobenzoxazoles on water under microwave irradiation. The product, 2-aminobenzoxazoles, was successfully produced via direct amination with various amines in moderate to high yields. The formal synthesis of Suvorexant, a medication for the treatment of insomnia, was accomplished using a developed amination process. The reaction was completed in an hour at 100–150 °C in a microwave reactor without the use of external catalyst or additive. Key benefi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
13
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 31 publications
(13 citation statements)
references
References 51 publications
0
13
0
Order By: Relevance
“…1) constitute a very interesting compound family due to their applications not only in organic synthesis, but also in the biomedical field as antibacterial, antiviral, anti-inflammatory, analgesic and anthelmintic agents. [13][14][15][16][17] Moreover, interesting studies have shown that the complexes of 2-mercaptobenzoxazoles with various transition metals possess a cytotoxic activity against cancer cells. 18…”
mentioning
confidence: 99%
“…1) constitute a very interesting compound family due to their applications not only in organic synthesis, but also in the biomedical field as antibacterial, antiviral, anti-inflammatory, analgesic and anthelmintic agents. [13][14][15][16][17] Moreover, interesting studies have shown that the complexes of 2-mercaptobenzoxazoles with various transition metals possess a cytotoxic activity against cancer cells. 18…”
mentioning
confidence: 99%
“…A catalyst-free protocol was reported to synthesise 2-aminobenzoxazole, through the amination of 2mercaptabenzoxazole. [61] The reaction was carried out under microwave irradiation at 100-150 °C for 1 h. On-water amination procedure made this approach eco-friendly and costeffective. Various substituted amines and benzoxazoles provided moderate to good yields of the required products.…”
Section: Catalyst-free Amination Of Benzoxazolementioning
confidence: 99%
“…A microwave enhanced catalyst‐free amination of 2‐mercaptobenzoxazoles 1 on water was developed by Wacharasindhu and co‐workers (Scheme ) . Addition of amine 2 to 1 generates adduct 5 as an intermediate.…”
Section: Cross‐coupling Reactionsmentioning
confidence: 99%